2014
DOI: 10.1016/j.bbi.2013.09.014
|View full text |Cite|
|
Sign up to set email alerts
|

Inflammatory dietary pattern and risk of depression among women

Abstract: Backround Inflammation is considered as a mechanism leading to depression, but the association between inflammatory dietary pattern and depression risk is unknown. Methods Using reduced-rank regression, we identified a dietary pattern that was related to plasma levels of inflammatory markers (C-reactive protein, interleukin-6, tumor necrosis factor α receptor 2), and we conducted a prospective analysis of the relationship of this pattern and depression risk among participants in the Nurses’ Health Study. A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
114
2
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(137 citation statements)
references
References 56 publications
(88 reference statements)
12
114
2
3
Order By: Relevance
“…In this large cohort, the Prudent (high in vegetables) or Western (high in meats) food patterns also identified by using principal component analysis did not show any significant association with the incidence of depression (44) . However, another posterior assessment in the Nurses' Health Study using reduced rank regression methods found that a pro-inflammatory food pattern was significantly associated with a higher risk of depression (45) supporting the hypothesis of the biological plausibility for the link between cardioprotective diets and reduced risk of depression mentioned earlier.…”
Section: Available Longitudinal Evidence On Food Patterns and The Rissupporting
confidence: 59%
“…In this large cohort, the Prudent (high in vegetables) or Western (high in meats) food patterns also identified by using principal component analysis did not show any significant association with the incidence of depression (44) . However, another posterior assessment in the Nurses' Health Study using reduced rank regression methods found that a pro-inflammatory food pattern was significantly associated with a higher risk of depression (45) supporting the hypothesis of the biological plausibility for the link between cardioprotective diets and reduced risk of depression mentioned earlier.…”
Section: Available Longitudinal Evidence On Food Patterns and The Rissupporting
confidence: 59%
“…As detailed in the previous section, B-vitamins are the source of coenzymes that participate in the one-carbon metabolism. Disruptions in this pathway can increase Hcys oxidized derivates that have toxic effects in the brain and the vascular endothelium, believed to be part of the disease aetiology (Baune et al, 2012;Bhat, 2009;Bottiglieri, 2013;Folstein, et al, 2007;Lucas, et al, 2014;Selhub, 2002).…”
Section: B Vitamins and Depressionmentioning
confidence: 99%
“…In nutrition epidemiology, the difficulties when searching for the impact of single nutrients have stimulated researcher's awareness to investigate the health effect of food item combinations that is food or dietary patterns (Barbaresko et al 2013;Lucas et al 2014;Martinez-Gonzalez & Bes-Rastrollo 2014). Dietary pattern is among the important factors in the promotion and maintenance of good health throughout the entire course of life (Marchini et al 2005).…”
Section: Introductionmentioning
confidence: 99%